2020
DOI: 10.2147/dmso.s238748
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adiposity Indicators as Cardio-Metabolic Risk Predictors in Adults from Country with High Burden of Obesity</p>

Abstract: Background: In Qatar more than 70% 0f the adults are overweight and obese. Different adiposity assessment methods have been proposed to identify individuals at cardio-metabolic risk. Purpose: This study aimed to compare anthropometric indicators with Dual-energy X-ray absorptiometry (DXA)-derived adiposity indicators in predicting cardio-metabolic risk among Qatari adults. Patients and Methods: A random sample of five hundred and fifty-eight (558) healthy Qatari adults (men and women) aged 20 to 50 years was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…These results were consistent with previous studies, demonstrating that WtHR was a valuable screening tool for adult cardiometabolic risk factors [ 27 ] and the most sensitive marker for predicting MetS [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with previous studies, demonstrating that WtHR was a valuable screening tool for adult cardiometabolic risk factors [ 27 ] and the most sensitive marker for predicting MetS [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…37,38 Interestingly, the predictive performance of the TyG index as an adiposity indicator has been reported in an Indian population, 39 as well as cardiometabolic risk predictor in an Arabian population. 40 The anthropometric amelioration and metabolic amelioration found in this study after energy restriction are similar to those reported in other comparable trials such as NUGENOB, 41 PREVIEW, 42 POUNDS LOST, 43 Look AHEAD 44 and DiRECT. 45 Accordingly, changes in weight, BMI and fat content after the 8 weeks of nutritional intervention were controlled by age, smoking status, cholesterol, blood pressure and daily physical activity.…”
Section: Discussionsupporting
confidence: 90%
“…47 Frequently, indicators of WC and WHR adipose tissue distribution within the body are recommended with regard to detecting obesity and determining overall health hazard, in view of the strong links between abdominal obesity and CVDs. 42,[47][48][49] The results of our study were based on adipose tissue measurement using the BIA method. To date, no clear cut-offs for BF% have been established for both obesity diagnosis, and CRFs risk prediction.…”
Section: Discussionmentioning
confidence: 99%